ANALYSIS OF PLANNING OF PREPARATION OF BLOOD FROM DONORS IN THE REPUBLIC OF KARAKALPAKSTAN (World Bulletin of Public Health, 2023)
In order to develop optimal methods for determining the need for blood components in medical institutions, plans and reports on blood procurement over the past 10 years, the number of beds by districts, population statistics, data on bed-days of treatment of patients in the Republic were analyzed and studied Karakalpakstan (RKK). Based on the studies and calculations, the norms for the collection of blood components over the past 10 years were determined and compared with the indicators planned and prepared by the RKK blood service. A large discrepancy between the planning of blood procurement from donors and the current regulatory documents was revealed. In order to review the methods for determining the need for blood, it was recommended to conduct separate studies in each narrow area.